Suburban neighbourhoods versus panel housing estates – An ecological footprint-based assessment of different residential areas in Budapest, seeking for improvement opportunities - Egedy, Tamás; Szigeti, Cecília; Harangozó, Gábor (Hungarian Geographical Bulletin, 2024)
In this study, the household consumption-related ecological footprint of lifestyles linked to panel housing estates and suburban neighbourhoods were compared in the case of Budapest and its suburbs. Our results show that the biggest parts of the ecological footprint are in both study areas the carbon, the cropland and the forest components, in line with earlier calculations. On the whole, the ecological footprint values are bigger in the suburban study area (2.63 gha/capita) compared to the panel housing estates (2.29 gha/capita), mainly because of the differences between the carbon uptake and the built-up land components. Beyond comparing the ecological footprint values of different residential areas, the study also contributes to the literature by addressing the improvement options of the respective areas through a rough model calculation on the reduction opportunities in both cases, resulting 36 percent in case of panel housing estates, and 47 percent in the suburban areas. Although these values have to be considered cautiously, they show significant opportunities in ecological footprint reduction in both types of residential areas supported by individual motivations, as well as by policy measures.